2006
DOI: 10.1007/s10608-006-9018-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Attribution Style, Child Abuse History, and PTSD Symptom Severity in Vietnam Veterans

Abstract: Relationships between learned helplessness, locus of control, child abuse histories, adult trauma exposure and subsequent PTSD symptom severity in a clinical sample of male Vietnam veterans were examined. Learned helplessness and external locus of control were not only reliably associated with each other, but also differentially associated with childhood abuse and PTSD symptom severity. Learned helplessness, in particular, evidenced significant relationships with both childhood trauma and current distress. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Several studies suggest that the helplessness concept has proven itself a useful model in the context of PTSD. That is, more PTSD symptoms seem to be related to a more pronounced disadvantageous attributional style (Elwood, Hahn, Olatunji, & Williams, 2009 ; McKeever, McWhirter, & Huff, 2006 ; McCormick, Taber, & Kruedelbach, 1989 ; Palker-Corell & Marcus, 2004 ). Moreover, there are some indices that individuals with trauma exposure face difficulties when they engage in goal-directed behavior in stressful situations (Weiss et al, 2012 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Several studies suggest that the helplessness concept has proven itself a useful model in the context of PTSD. That is, more PTSD symptoms seem to be related to a more pronounced disadvantageous attributional style (Elwood, Hahn, Olatunji, & Williams, 2009 ; McKeever, McWhirter, & Huff, 2006 ; McCormick, Taber, & Kruedelbach, 1989 ; Palker-Corell & Marcus, 2004 ). Moreover, there are some indices that individuals with trauma exposure face difficulties when they engage in goal-directed behavior in stressful situations (Weiss et al, 2012 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Research has found that external LOC is related to higher level of PTSD-symptoms (e.g. Casella & Motta, 1990;McKeever, McWhirter, & Huff, 2006;Norris et al, 2002;Solomon, Mikulincer, & Avitzur, 1988, Zhang et al, 2014. Hence, internal LOC is expected to be a protective factor against PTSD, while an external LOC is a risk factor for the development of PTSD after exposure to combat.…”
Section: Locus Of Control and Ptsdmentioning
confidence: 99%
“…Studies have also shown the relevance of self-efficacy as a predictor of PTSD (Benight et al, 2000;Flatten, W€ alte, & Perlitz, 2008;Pooley, Cohen, O'Connor, & Taylor, 2012). Regarding locus of control, researchers have demonstrated a relation between locus of control and PTSD, with an internal LOC associated with a resistance to PTSD development (Leiderman-Cerniglia, 2002) and external LOC with the development and maintenance of PTSD (McKeever, McWhirter, & Huff, 2006). Several authors found a positive relationship between external locus of control and greater current levels of PTSD symptom severity (Mellon, Papanikolau, & Prodromitis, 2009;Shaw, 2000).…”
Section: Practitioner Pointsmentioning
confidence: 99%